Differential transcriptional regulation of the apoAI gene by retinoic acid receptor homo- and heterodimers in yeast. - Salerno, A J (1996)
Several members of the nuclear receptor superfamily including RXR (retinoid X receptor) bind to a specific retinoic acid response element (site A) of the apoAI promoter. However, transcriptional activation of the apoAI gene by different homo- and heterodimeric forms of RXR or RAR (retinoic acid receptors) cannot be evaluated in mammalian cells, which contain endogenous RXR or RAR. In order to circumvent this limitation, we assessed the DNA-binding activities and transcriptional activation of different homo- and heterodimers of these receptors in yeast. Electrophoretic mobility shift assays (EMSA) demonstrated that yeast expressed RARalpha does not bind to site A of the apoAl promoter, whereas binding of RARbeta to site A is ligand-dependent. Both RARalpha and RARbeta form heterodimers with RXRalpha and bind to site A with high affinity. These DNA-binding studies correlate with the transcriptional data, which indicated that RARbeta but not RARalpha activates transcription from site A in response equally well to 9-cis and all-trans retinoic acids. 9-cis RA is a more potent ligand than all-trans RA to activate transcription via RXR/RAR heterodimers. We conclude that this yeast expression system is a useful tool to elucidate the 'transactivation code' for apoAl site A via specific combinations of different homo and heterodimeric versions of RXR and RAR.